Assistance in Preparing Final Reports for Educational Internship Students at SMA Negeri 01 Buay Madang - Sugiarti (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
Assistance in making final reports for educational internship students at SMA Negeri 01 Buay Madang includes several key points. Students who undertake educational internships at these schools have valuable experience in observing, interacting, and contributing to the educational environment. The final report reflects students' in-depth understanding of the learning process, school management, and the dynamics of teacher-student relationships at the high school. In the report, students present an evaluation of learning methods, challenges faced, and recommendations for improvement. Apart from that, student assistance also includes understanding the school curriculum and student involvement in extracurricular activities. In conclusion, the intern students succeeded in integrating educational theory with practice in the field, proving their professional growth and contribution to educational development at SMA Negeri 01 Buay Madang.